2021
DOI: 10.1016/j.omtn.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of cRGD conjugation at 5′-antisense strand of siRNA by phosphodiester linkage extension

Abstract: Small interfering RNAs (siRNAs) are widely studied for their highly specific gene silencing activity. However, obstacles remain to the clinical application of siRNAs. Attaching conjugates to siRNAs can improve their stability and broaden their application, and most functional conjugates of siRNAs locate at the 3 0 -terminus of the sense or antisense strand. In this work, we found that conjugating a group at the 5 0 -terminus of the antisense strand via phosphodiester was practicable, especially when the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Lipid nanoparticles are one of the most attractive and advanced delivery system tools and are commonly used to encapsulate DNA, siRNA, and mRNA. , Herein, we developed a multivalent mRNA vaccine platform based on various mRNA sequences encapsulated with LNPs to fight against SARS-CoV-2 and its variants. The RBD sequences of SARS-CoV-2 Wuhan-Hu-1, Delta and Omicron variants (amino acids 319–541) were designed as the antigen coding regions, as revealed in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid nanoparticles are one of the most attractive and advanced delivery system tools and are commonly used to encapsulate DNA, siRNA, and mRNA. , Herein, we developed a multivalent mRNA vaccine platform based on various mRNA sequences encapsulated with LNPs to fight against SARS-CoV-2 and its variants. The RBD sequences of SARS-CoV-2 Wuhan-Hu-1, Delta and Omicron variants (amino acids 319–541) were designed as the antigen coding regions, as revealed in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the pH-responsiveness ability of DDA-SS-DMA and the effectiveness of the LNP delivery system, a lysosome escape assay was carried out. , Briefly, PC-3 cells were added to a confocal culture dish (14 mm), and after 20 h of proliferation, these cells reached 80% confluence. Afterward, fluorescein isothiocyanate (FITC)-labeled formulations were added to the confocal culture dish followed by the culture at 37 °C for varying times (2, 4, and 6 h).…”
Section: Materials and Methodsmentioning
confidence: 99%
“… 37 Previous studies have shown that DCP (cytidinyl/cationic mixed lipids, DNCA/CLD/DSPE-PEG, Table S1 ), a novel transfection system based on hydrogen bonding and π-π stacking, can deliver various ON drugs into cells with high efficiency. 38 , 39 , 40 , 41 , 42 , 43 The combined encapsulation effect of various intermolecular forces makes the ratio of the formulation components more flexible depending on the context, and the cationic lipid levels can be negligible. Compared with sorafenib, DCP-CT102 achieved greater efficacy at a dose of ∼2 mpk administered every other day.…”
Section: Introductionmentioning
confidence: 99%